Metabolic Versatility and Antibacterial Metabolite Biosynthesis Are Distinguishing Genomic Features of the Fire Blight Antagonist Pantoea vagans C9-1 - Smits, Theo H. M. (Public Library of Science, 2011)
BACKGROUND: Pantoea vagans is a commercialized biological control agent used against the pome fruit bacterial disease fire blight, caused by Erwinia amylovora. Compared to other biocontrol agents, relatively little is currently known regarding Pantoea genetics. Better understanding of antagonist mechanisms of action and ecological fitness is critical to improving efficacy. PRINCIPAL FINDINGS: Genome analysis indicated two major factors contribute to biocontrol activity: competition for limiting substrates and antibacterial metabolite production. Pathways for utilization of a broad diversity of sugars and acquisition of iron were identified. Metabolism of sorbitol by P. vagans C9-1 may be a major metabolic feature in biocontrol of fire blight. Biosynthetic genes for the antibacterial peptide pantocin A were found on a chromosomal 28-kb genomic island, and for dapdiamide E on the plasmid pPag2. There was no evidence of potential virulence factors that could enable an animal or phytopathogenic lifestyle and no indication of any genetic-based biosafety risk in the antagonist. CONCLUSIONS: Identifying key determinants contributing to disease suppression allows the development of procedures to follow their expression in planta and the genome sequence contributes to rationale risk assessment regarding the use of the biocontrol strain in agricultural systems.